Study Of Organizational Culture And Its Impact On Creativity In Malaysian SMES - Maroofiyan, Mitra (2011)
The success of organizations depends on the proper match between individuals and organizational culture. Mangers need an accurate realization of the culture on their organization to direct parties in the best and most efficient way. Therefore, managers should have a clear understanding of the organizational culture and factors influencing it. Further, they will be able to manage creativity by cultural aspects of the organizations when they are able to identify the most influential factors of the culture. As a result, this study aims to identify these factors and highlight the most important ones which impact creativity in Malaysian SMEs.